« Mr Azn@r, parT » - Ludivine Thouverez (Amnis)
The attacks of the 11th of march in Madrid provoked a division between the mass media and the Spanish society. By only repeating the discourse of the government (which blamed ETA to win the elections) the media did not manage to provide a plural and free information of the res publica. During the crisis, the NTIC, new technologies of information and communication, turned into a mediatic and social counterpart. The horizontal communication made possible the expression of different opinions and the NTIC helped to mobilize the citizens on the day before the elections. Can the union NTIC - civil society stop the manipulation of the information? Can it lead to a greater transparency and revolutionize the democracy? The terrorism and its mediatic coverage are rather complex. They are based on opposed interests and are produced in a socio-political context which determinates the press discourse's about terrorism. If the new technologies amply the public space of debate, they do not offer many solutions to the problems of the journalists when they have to focus terrorism.